PENGARUH REFLEKSI DIRI KRITIS TERHADAP KESIAPAN MENGAJAR MAHASISWA CALON GURU MELALUI PENGALAMAN OBSERVASI SEKOLAH - Dwi Lestari, Ita; Ersi Anggita, Ana; Emilia, Wulan; Netriwati; Nendra, Fadly (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of critical self-reflection on the teaching readiness of pre-service teachers and to examine the differences in teaching readiness before and after observation activities. The study employed a quantitative approach with a pretest–posttest design. Data were collected using questionnaires measuring teaching readiness at the pre- and post-observation stages, as well as critical self-reflection at the post-observation stage. Data analysis was conducted using descriptive and inferential statistics with the assistance of SPSS, including the Paired Sample t-Test and simple linear regression. The results showed that there was no significant difference in teaching readiness before and after observation (Sig = 0.343 > 0.05), although there was an increase in the mean score. However, the regression analysis indicated that critical self-reflection had a significant effect on teaching readiness (Sig = 0.000 < 0.05), with a coefficient of determination of 0.632. This finding suggests that critical self-reflection makes a strong contribution to students’ teaching readiness. These findings indicate that observation activities alone are insufficient to significantly improve teaching readiness without being accompanied by a process of critical self-reflection. Therefore, the integration of structured reflective activities in pre-service teacher education is essential to optimally enhance teaching readiness.